Солонгос хэлний үнэлгээ, шалгалтын аргачлал (Солонгос хэлний түвшин тогтоох шалгалтын жишээгээр): Korean language evaluation and test-taking strategies (Focused on test of proficiency in korean ) - L., Tserenkhand; S., Enkhchimeg (Mongolian Journal of Foreign Languages and Cultures, 2023)
Test of Proficiency in Korean is co-organized by Department of Asian Studies of NUM and Korean National Institute for International Education and the 46th TOPIK is on the run. Due to the rising number of test takers more and more TOPIK courses are emerging. TOPIK trainers are facing many issues on running the test preparation course including the test knowledge, experience and strategies. For this reason, we did research on TOPIK and developed some strategies for students to answer the test questions. We aimed to invent strategies based on the study about the contents of the TOPIK, test takers’ results analysis and test questions.